Acute Events in Primary Health Care Settings: An Analysis of Advanced Practice Competencies in Nursing Consultations in Brazil - Marília Orlandelli Carrer; Letícia Yamawaka deAlmeida; Andrea Liliana Vesga‐Varela; Daiana Bonfim; Patrícia Aline deAlmeida; Carla Pereira Barreto; Nayara Vilela deFarias Serranegra; Keila Gisele Lima Reis; Claudia Santos Martiniano; Manoel Vieira Miranda Neto (Nursing Open)
ABSTRACT Aims To describe nurse practices during acute event nursing consultations in Primary Health Care settings and analyse whether these professionals demonstrate the competencies proposed for Advanced Practice Nurses within a care management scope. Design A multicenter, exploratory, cross‐sectional study employing both quantitative and qualitative analysis. Methods Data were collected through direct non‐participatory observations (film footage of nursing consultations) and medical record analysis. The study included 28 nurses and 203 patients from 17 primary care units across four municipalities in Brazil. Descriptive statistical analysis was applied to quantitative data, while qualitative data underwent content analysis. Results Challenges were observed in performing the nursing process and clinical communication during nursing consultations. Some of the proposed competencies for Advanced Practice Nurses were partially applied within a care management framework in Primary Health Care settings. The competencies related to the focus on care (61.11%), care provision (41.20%) and assessment and diagnosis (40.50%) were notable, with an overall average of 47.60% competency identification across all three dimensions. Although some general advanced practice nurse competencies were observed, their application was often limited or inconsistent. Conclusion This study identified limitations in nursing consultations for acute events in Primary Health Care, particularly regarding the nursing process and the application of Advanced Practice Nurse competencies. Notable gaps were observed in areas such as cultural diversity and advanced assessment skills. Future efforts should focus on developing educational programmes, providing resources and creating clinical guidelines to enhance current nursing practices and facilitate the implementation of Advanced Practice Nursing in Brazil. Impact The results provide empirical evidence to inform policy decisions, educational programmes, nursing practices and planning for advanced practice nursing implementation in Brazil. These findings are particularly relevant for healthcare educators, researchers, regulatory institutions and managers aiming to enhance the effectiveness of nursing consultations for acute events. Reporting Method This paper adheres to the COREQ and STROBE checklist. Patient or Public Contribution No patient or public contributions.